2017
DOI: 10.1016/j.crma.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A variational principle in the parametric geometry of numbers, with applications to metric Diophantine approximation

Abstract: Abstract. We establish a new connection between metric Diophantine approximation and the parametric geometry of numbers by proving a variational principle facilitating the computation of the Hausdorff and packing dimensions of many sets of interest in Diophantine approximation. In particular, we show that the Hausdorff and packing dimensions of the set of singular m × n matrices are both equal to mn 1 − 1 m+n , thus proving a conjecture of Kadyrov, Kleinbock, Lindenstrauss, and Margulis as well as answering a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 16 publications
1
63
0
Order By: Relevance
“…. When min{m, n} 2, important contributions towards Problem 2 are announced without proofs by T. Das, L. Fishman, D. Simmons and M. Urbański, see [13]. Tedious calculation shows that the lower bound given in Theorem 3 agrees with the formula given in [13, theorem 1•9].…”
Section: Theorem 1 For Any Real Numbermentioning
confidence: 73%
See 1 more Smart Citation
“…. When min{m, n} 2, important contributions towards Problem 2 are announced without proofs by T. Das, L. Fishman, D. Simmons and M. Urbański, see [13]. Tedious calculation shows that the lower bound given in Theorem 3 agrees with the formula given in [13, theorem 1•9].…”
Section: Theorem 1 For Any Real Numbermentioning
confidence: 73%
“…Kadyrov et al [20] established that this dimension is bounded from above by mn(m + n − 1)/(m + n) and it is conjectured that there is in fact equality. In [13], Das et al announced a proof of this conjecture as a consequence of a "variational principle".…”
Section: Theorem B the Hausdorff Dimension Of The Set Of Singular Twmentioning
confidence: 98%
“…In[2,3], Das, Fishman, Simmons and Urbański introduce a variational principle in parametric geometry of numbers that extends Theorem 2. They both extend to the case of approximation to a matrix θ, and provide a quantitative result.…”
mentioning
confidence: 99%
“…, α n , 1} linearly independent over Q exist if n > 1. It has recently been shown that when n > 1 the set of singular α ∈ R n has Hausdorff dimension n 2 n+1 (see [3], [4], and [6]). The Minkowski chain also gives a criterion for L α to be singular.…”
Section: Applications To Diophantine Approximationmentioning
confidence: 99%